Sport-Specific Functional Tests and Related Sport Injury Risk and Occurrences in Junior Basketball and Soccer Athletes. (11th December 2020) - Chang, Wen-Dien; Lu, Chi-Cheng
Abstract : Objectives . Sport-specific functional tests were used to assess the power, speed, and agility of the lower extremity for a specific sport, but comparison of the differences and association with sport injury was rare. The aim of this study was to investigate the differences in sport-specific functional tests between junior basketball and soccer athletes and analyze the sport injury risk and occurrences. Methods . All participants were evaluated using the sprint test, vertical jump (VJ) test, agility T test, and functional movement screen (FMS). There were significant intergroup differences in the sprint test, VJ test, agility T test, and FMS. Specific functional tests were compared against FMS score, either FMS ≤ 14 or FMS > 14 . The FMS subtests, namely, in-line lunge, trunk stability push-up (TSPU), and quadruped rotary stability, were also performed. In one-year follow-up, the sport injury incidence was also recorded. Results . Significant differences in sprint, agility, and FMS performance were found between the junior basketball and soccer athletes. Individual FMS scores of the in-line lunge, TSPU, and quadruped rotary stability were evaluated. No significant differences in sprint, VJ, and agility scores were found between FMS ≤ 14 and FMS > 14 . FMS total score ≤ 14 was significantly associated with high sport injury occurrence. Conclusions . The scores of sprint, agility, and FMS performance were differed between basketball and soccer athletes. The scores of sprint, VJ, and agility tests did not have differences with sport injury risks and occurrences, but the FMS score was associated with sport injury occurrence.